Comparison machining performance of Al2 O3 , ZTA and ZTA doped Cr2 O3 cutting tools on AISI 1045 - T., Norfauzi; A. B., Hadzley; U. A. A., Azlan; M. M., Faiz; M. F., Naim; A. A., Aziz (IOP, 2019)
This paper presents the comparison of machining performance for cutting tools that fabricated by pure alumina (Al2O3), Zirconia Toughened Alumina (ZTA) and Zirconia Toughened Alumina doped with Cr2O3 (ZTA Doped Cr2O3). Solid-state method was employed to prepare ceramic mixtures starting from 12 h ball milling with 40 rpm rotational speed. The green bodies were formed by 5 ton manual hydraulic press and 300 MPa Cold Isostatic Press (CIP) compaction pressure. The compacted powders then were sintered at 1400 °C and 9 h soaking time in the form of RNGN 120600 designated cutting tools. Properties assessment of the fabricated cutting tools were analysed based on hardness and density. The machining evaluation was performed by turning AISI 1045 with cutting speeds of 150–350 m min−1, feed rate of 0.125 mm/rev and depth of cut of 0.5 mm. The results show that maximum hardness recorded for ZTA Doped Cr2O3 with 13.73 GPa Vickers hardness and 3.82 g cm−3 density, followed by ZTA (12.75 GPa, 3.85 g cm−3) and pure Al2O3 (4.9 GPa, 3.76 g cm−3)In terms of machining performance, ZTA Doped Cr2O3 recorded highest tool life of 330-s with 57% improvement of tool life as compared to ZTA (210-s) and 200% improvement of pure Al2O3 (110-s). Dominant wear mechanisms for the fabricated cutting tool appeared to be notch wear, abrasive wear and chipping at the flank wear area.